Cause‐related events: fulfilling the objectives of social partnerships. Issue 4 (29th June 2016) - Lyes, Amy; Palakshappa, Nitha; Bulmer, Sandy
Abstract : Cause‐related events are growing in frequency and popularity. These events enable corporates and not‐for‐profit organisations to collaborate for mutual benefit, within the strategic framework of a social partnership. However, while anecdotal evidence indicates that millions of dollars are invested in events, less is known about how the strategic objectives of social partnerships are achieved via cause‐related events. We present the findings of an ethnographic study of two social partnerships and contribute insights into how and why events help them achieve their strategic objectives. Case analysis data reveals that the fit between events and partnerships; the people, teams, and relationships; and collaboration of resources all contribute to generating competitive advantage and value. We discuss the managerial implications for those collaborating to organise a cause‐related event. Copyright © 2016 John Wiley & Sons, Ltd.